High CIB1 expression in colorectal cancer liver metastases correlates with worse survival and the replacement histopathological growth pattern - Shuang Fan; Johannes Robert Fleischer; Lolita Dokshokova; Lena Sophie Böhme; Gwendolyn Haas; Alexandra Maria Schmitt; Fabio Bennet Gätje; Linde-Allegra Emmalie Rosen; Hanibal Bohnenberger; Michael Ghadimi; Baolong Cui; Xingbo Xu; et al. (Molecular Therapy: Oncology)
To date, nearly one-quarter of colorectal cancer (CRC) patients develop liver metastases (CRCLM), and its aggressiveness can be correlated to defined histopathological growth patterns (HGP). From the three main HGPs within CRCLM, the replacement HGP emerges as particularly aggressive, characterized by heightened tumor cell motility and vessel co-option. Here, we investigated the correlation between the expression of calcium- and integrin-binding protein 1 (CIB1), a ubiquitously expressed gene involved in various cellular processes including migration and adhesion, and disease-free (DFS) and overall survival (OS) in primary CRC patients. Additionally, we explored the correlation between CIB1 expression and different HGPs of CRCLM. Proteomic analysis was used to evaluate CIB1 expression in a cohort of 697 primary CRC patients. Additionally, single-cell and spatial RNA-sequencing datasets, along with publicly available bulk sequencing data were used to evaluate CIB1 expression in CRCLM. In silico data were further validated by formalin-fixed paraffin-embedded immunohistochemical stainings. We observed that high CIB1 expression is independently associated with worse DFS and OS, regardless of Union Internationale Contre le Cancer stage, gender, or age. Furthermore, the aggressive replacement CRCLM HGP is significantly associated with high CIB1 expression. Our findings show a correlation between CIB1 levels and the clinical aggressiveness of CRC. Moreover, CIB1 may be a novel marker to stratify HGP CRCLM.